Development and Optimization of an Urban-Scale Omnidirectional Wind Turbine with Integrated Solar Power System - Muhamad Aiman Ahmad Erawan,; Faridah Hanim Mohd Noh, (Progress in Engineering Application and Technology, 2026)
Renewable energy sources are very important for the preparation for the shift from the fossil fuel. This study introduces the design and optimization of city wide hrbrid renewable energy system between wind turbine and solar system [1]. The design aims at efficiently the turbulent and multidirectional urban wind, and supplementing energy generation with solar power on low wind conditions to ensure stable and continous output. Much emphasis has been given to design optimization, selection of materials, durability, cost-effectiveness, and easy installation in densely packed urban cities. Its compact hybrid design demonstrates strong potential for deployment in smart cities and sustainable urban energy infrastructure.